Amphiphilic copolymer aqueous solutions with cholinium ionic liquids as adjuvants: New insights into determination of binodal curves and phase-separation mechanisms - Kurnik, Isabelle S. [UNESP]; Mussagy, Cassamo U. [UNESP]; Pereira, Jorge F.B. [UNESP]; Lopes, André M. (Elsevier, 2020)
Aqueous two-phase micellar systems (ATPMS) are more than simple amphiphilic copolymer or surfactant aqueous solutions since due to the formation of biphasic regimes, at certain temperatures, these can be successfully used for the separation, encapsulation, and formulation of several bio-based compounds. The recent use of ionic liquids (ILs) as adjuvants in the formation of ATPMS have enlarged its “working window”, but the measurement of respective binodal curves is still very empiric and dependent of operator accuracy through the visual determination of cloud-point temperature. In this work, the range of ATPMS using ILs as adjuvants was extended, providing more insights about their phase formation mechanisms, as well as into determination of cloud-point values of the lower critical solution temperature (LCST)-type demixing transition by using the new temperature modulated optical refractometry approach. The binodal curves of ATPMS composed of Pluronic® L35/PBS buffer at pH 7.4 + cholinium ILs were determined, by using two different methods, i.e.: cloud-point temperature (TCP) visual determination versus temperature modulated optical refractometry (TMOR). TMOR method was more sensitive to the determination of biphasic transition, particularly, in highly diluted solutions (< 3.0 wt% of Pluronic L35). The results also established that the addition of cholinium ILs decreased significantly the phase separation temperatures of Pluronic L35/PBS, with an increase of biphasic region (viz. lower of TCP values) as a function of the relative hydrophobicity of the IL anion, i.e.: [Hex]− > [But]− > [Pro]− > [Ac]− > Cl−. The use of cholinium ILs as adjuvants is particularly important to provide mild conditions for ATPMS-based separation and encapsulation strategies, while TMOR-based methods allow an improvement of phase separation determination accuracy.
Keywords: Aqueous two-phase micellar systems (ATPMS); Cloud-point temperature; Ionic liquids (ILs); Phase separation; Refractometry; Temperature modulated optical refractometry (TMOR)